Status and Potential of Tree Borne Oilseeds (TBOS) in Biofuel Production of India - Punia, M.S.; Kureel, R.S.; Pandey, Ashutosh (Indian Journal of Agroforestry, 2020)
Survey of potential areas for identification of superior planting material of Jatropha curcas and Pongamia pinnata was conducted by 31 and 10 participating centers respectively by NOVOD during 2005-06 in more than 140 districts of 21 states. More than 1758 superior trees having seed yield of 2.0 to 4.0 kg/plant and more than 30% oil content have been identified for Jatropha curcas and about 432 CPTs have been identified for Pongamia pinnata. The oil percentage in the selected CPTs of Jatropha curcas ranged from 28-48% and the test weight (100 seeds) ranged from 20.7 to 77.1 g. The oil content more than 35% have been found in 117 seed samples of Karanja, out of 323 samples as against the average oil content of 20-25%. These TBOs possesses 20-60% oil content in seeds, which is non-edible and can be utilized as a source of bio-diesel production.